A systematic review of the questionnaire used in oral health knowledge, attitudes, and practices in 12 years old children in the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University - Sri P. Utami; Intan BE. Mahata; Hamdy Lisfrizal (Journal of Dentomaxillofacial Science, 2022)
Objective: The purpose of this study was to determine a systematic review of the questionnaire used on oral health knowledge, attitudes, and practices in children aged 12 years in the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University. Methods: This type of research is a descriptive analytic study with are search design cross sectional. The population of this study was 12 year old children who came to the Paedodonti Department of Baiturrahmah Hospital in January 2020-March 2020 with a total sample of 68 people. The research was conducted at the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University in January 2020-March 2020 using a questionnaire. The data obtained from this study were analyzed statistically using the application SPSS with descriptive analysis. Results: The results showed that the kueisoner review at the level of knowledge and attitude was very good, while the action was quite good. Conclusion: The conclusion of this study is where the level of knowledge and attitudes of 12 year olds at Dental Hospital Department of Pediatric Dentistry Baiturrahmah University, is already very good, while the actions pretty good. Knowledge, attitudes and actions of all these components play an important role in influencing the level of dental and oral hygiene in children.